Unveiling the photovoltaic properties of ETL-free, lead-free, and graphene-based PSC - Jalaludin N.A.; Salehuddin F.; Arith F.; Zain A.S.M.; Kaharudin K.E.; Junos S.A.M.; Ahmad I. (Institute of Electrical and Electronics Engineers Inc., 2025)
The entire photovoltaic field has recently experienced significant achievement in perovskite solar cell (PSC) research with remarkable progress in device performance and power conversion efficiency (PCE). High-performance perovskite solar cells typically utilize n-i-p and pi-n device structures, with separate electron transport layer (ETL) and hole transport layer (HTL), which are considered as necessary components for effective photogenerated carrier extraction. However, conventional PSCs are sensitive to heat, humidity, and light leading to prolonged instability. Herein, an ETL-free approach was investigated, combining lead-free methylammonium tin triiodide (MASnI3) as the absorber with graphene oxide (GO) as the HTL. The study yielded notable results with a PCE of 17.83%. The insights revealed in this research have the potential to be applied in the development of cost-effective ETL-free PSCs with enhanced performance. ? 2024 IEEE.